2019
DOI: 10.1002/ana.25565
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of skin innervation is associated with a severe fibromyalgia phenotype

Abstract: Objective: To assess patterns and impact of small nerve fiber dysfunction and pathology in patients with fibromyalgia syndrome (FMS). Methods: One hundred seventeen women with FMS underwent neurological examination, questionnaire assessment, neurophysiology assessment, and small fiber tests: skin punch biopsy, corneal confocal microscopy, microneurography, quantitative sensory testing including C-tactile afferents, and pain-related evoked potentials. Data were compared with those of women with major depressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
154
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 116 publications
(174 citation statements)
references
References 43 publications
6
154
2
Order By: Relevance
“…Small (intraepidermal unmyelinated nerve fibers) and even large peripheral nerve fiber neuropathy, usually in distal body parts, has been observed in a proportion of FMS patients, leading to a lower density of these fibers in comparison with healthy individuals [ 5 , 6 , 45 48 ]. A recent study in a large cohort of patients with FMS applied different tests for multidimensional characterization of neuropathy, observing indications of widespread small nerve fiber dysfunction and damage and identifying patient subgroups in relation to the extent and pattern of this damage [ 49 ]. The reduced small fiber density is congruent with the increased rate of neurologic symptoms like numbness, tingling, and increased heat and cold sensorial thresholds in FMS patients [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Small (intraepidermal unmyelinated nerve fibers) and even large peripheral nerve fiber neuropathy, usually in distal body parts, has been observed in a proportion of FMS patients, leading to a lower density of these fibers in comparison with healthy individuals [ 5 , 6 , 45 48 ]. A recent study in a large cohort of patients with FMS applied different tests for multidimensional characterization of neuropathy, observing indications of widespread small nerve fiber dysfunction and damage and identifying patient subgroups in relation to the extent and pattern of this damage [ 49 ]. The reduced small fiber density is congruent with the increased rate of neurologic symptoms like numbness, tingling, and increased heat and cold sensorial thresholds in FMS patients [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…This has been demonstrated in adult studies using objective testing methods, such as pain-related evoked potentials, quantitative sensory evaluations and examination of skin biopsies using electron microscopy [21,22]. A metaanalysis indicates a 49% prevalence of small nerve fiber pathology in adult patients with FM [23] and recent evidence suggests that this may be related to symptom severity [24]. Aberrant expression of systemic and cutaneous microRNAs (which regulate molecular factors determining nerve de-and re-generation) were found to correlate with reduced density of small nerve fibers in patients with FM [25].…”
Section: Altered Pain Processingmentioning
confidence: 94%
“…In recent studies, small nerve fiber pathology was found in subgroups of patients with fibromyalgia syndrome (FMS) . Applying corneal confocal microscopy (CCM), corneal denervation was also reported in FMS patients …”
Section: Introductionmentioning
confidence: 99%